Diagnostic Utility of Separate Anti-Ro60 and Anti-Ro52/TRIM21 Antibody Detection in Autoimmune Diseases - Robbins, Ailsa; Hentzien, Maxime; Toquet, Segolene; Didier, Kevin; Servettaz, Amelie; Pham, Bach-Nga; Giusti, Delphine (Frontiers in Immunology, 2019)
Anti-SS-A antibodies are often sought for in autoimmune diseases diagnosis. Two different target proteins have actually been identified: Ro52 and Ro60. Clinical and immunological associations seem different depending on anti-Ro52 or anti-Ro60 antibodies presence. However, due to a heterogeneous presentation in the literature, some immunology laboratories in France have stopped providing anti-Ro52 antibody findings. We report here a new hospital study designed to determine the diagnostic utility of the separate detection of anti-Ro52 and anti-Ro60 antibodies. We conducted a retrospective, observational study, including every adult patient with positive antinuclear antibodies (ANA) tested in our immunology laboratory, and associated with anti-Ro52 and/or anti-Ro60 antibodies, between 2011 and 2014. Out of 13032 sera tested for ANA, 399 adults had antibodies to Ro52 and/or Ro60; 81.7% were female, with a mean age of 54.5±17.0 years. Anti-Ro52 antibodies were found in 75.7% of the patients and anti-Ro60 antibodies in 56.9%. Among them, 43.1% were classified in the Ro52+Ro60- group, 32.6% in the Ro52+Ro60+ group and 24.3% in the Ro52-Ro60+ group. In the Ro52-Ro60+ group, systemic lupus was the most frequent diagnosis (48.5%), with a possible association with antiphospholipid antibodies (anti-cardiolipin antibodies: OR 2.5 (CI95 [1.0-5.0], p=0.05) and lupus anticoagulant (OR 3.6 (CI95 [1.10-10.0] p=0.02)). In the Ro52+Ro60+, primary Sjögren Syndrome was the most likely (OR 4.2 95% CI [2.1-8.3] p<10-4), especially in patients Ro52+Ro60+La+. Patients with isolated anti-Ro52 had a wider variety of diseases associated, but among auto-immune diseases they were more prone to inflammatory myositis (OR 10.5 [1.4-81.7], p=0.02) and inflammatory rheumatism (OR 4.6 [1.6-13.8], p=0.006) in contrast to systemic lupus (OR 0.2 [0.1-0.3], p<10-4) or primary Sjögren’s syndrome (OR 0.1 [0.06-0.2], p<10-4). We therefore suggest that, when anti-ENA antibodies are prescribed, it should include separate anti-Ro52 and anti-Ro60 antibodies determination. To go even further, we would like to suggest a change in ENA nomenclature to avoid confusion, abandoning the anti-SS-A label in favor of the anti-Ro52/TRIM21 or anti-Ro60 antibody for a clearer designation.